PEMERTAHANAN BAHASA JAWA OLEH SUKU JAWA YANG BERDOMISILI DI GEDONG AIR BANDARLAMPUNG - WAHONO, WAHONO (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
The reality is that many people who continue to use her native language (mother tongue) in a new pluralistic society because they have difficulty learning a new language and other reasons, namely the origin of language he used is still used by local communities.Village Water Gedong Bandarlampung a village inhabited by the Java community as a participant migrants since 1967. They live in groups in a village or a district. In daily life he uses the language of origin (mother tongue) them, namely the Java language. However, he is faced with the environment of other villages who speak Lampung. Therefore, in berkomunikasi with local communities to use their National language. National languages are only used in official situations and is used to communicate with other communities. The method used is descriptive method, the data collected is described as it is then analyzed and conclusions drawn from the results of analysis of existing data. Research carried out by directly observing the activity of public speaking and interviews with Air gedong Bandarlampung. Based on research results, the conclusion that the Java language is still used by people gedong Water. Such use can be seen from several domains, among others: the family domain, education domain, domain trading, domain places of worship, and government domains. The results showed that the public water Gedong Bandarlampung 80% using the Java language as their mother tongue. This is done in the concept of retention of the language as a means of communication among members of society. The analysis showed that the Java language users spread across various groups, namely children, adolescents, and parents.Keywords: native language,Â  Java language, sosiolinguistict